Determination of Forces Affecting the Inclined Well - Mejidova , A.N. (Herald of Azerbaijan Engineering Academy, 2021)
While drilling the vertical part of the inclined well, the Fishtail drill bits (PX) with blades are often used. In the geological section of field, the inclined strata with different physical and mechanical properties are often encountered, i.e., of various strengths. It is known that soft rocks are easier to break down than hard ones. If one side of the Fishtail drill bit blade hits hard rock, then the deepening on the soft rock side is faster than in hard rock. Resistance force, i.e. the reaction force from hard rocks will be greater than from soft rocks, and as a result, a bending moment occurs on the bit, leading to the curvature of the wellbore toward soft rocks. To prevent borehole curvature, it is necessary to recalculate the operating parameters of drilling in the direction of decreasing the axial load on the bit. This barks the ability to reduce the difference between the reaction forces from both soft and hard rocks, which significantly reduces the bending moment on the bit. The process has been repeatedly proven in practice.